Students’ attitudes towards the usage of Bahasa Melayu in ESL classrooms / Mohd Ridzwan Rulam Ahmad - Rulam Ahmad, Mohd Ridzwan (2011)
The study investigated the students’ attitudes towards the usage of Bahasa Melayu in ESL classrooms. This study involved 60 Form 5 students from Sekolah Menengah Kebangsaan Sungai Pusu, Gombak, Selangor. The findings of the study indicated that the majority of students have positive attitudes towards L1 which is Bahasa Melayu to be employed in the English language class. Besides that, the findings also revealed that most of the students preferred using Bahasa Melayu in English class depending on the needs and the specific purposes such as for the grammar explanation, vocabulary translation, clarification of difficult activities and other purposes which could help the students to enhance their learning process towards the second language acquisition. However, the teacher should be aware of the excessive usage of L1 in ESL classrooms which sometimes could hinder the second language mastery among the students. Recommendations for future studies and solutions were discussed in order to give a clearer view for the teachers in implementing suitable approaches and methods in ESL classrooms.